Innovative Grammar Teaching: The Integration of Problem-Based Learning (PBL) and ESLVideo.com in Vocational School Context - Azizah, Annisa Nur; Jamilah (Institut Agama Islam Negeri Palopo, 2025)
Mastering grammar is often perceived as a difficult task for students, especially when they are passive during lectures that do little to ignite their interest. This research aimed to improve students’ grammar mastery of automotive engineering at SMKN 2 Depok Yogyakarta by combining Problem-Based Learning (PBL) with the ESLVideo.com. Concerning innovative approaches incorporating technology in teaching vocational school, the research was designed as Classroom Action Research (CAR) and was conducted in two cycles. 36 students from the 11th grade were purposively selected because they experience problems with grammar, a lack of motivation, and exposure to technology. These data were collected using pre-tests, post-tests, observation check-list, field notes, and interviews that employed qualitative and quantitative techniques. Paired-sample t-tests analyzed the quantitative data while qualitative data observations and interview provided the context in which the participants were engaged and challenges faced. The use of expert validation, triangulation, and statistical analysis served to enhance the validity and reliability of the research. The results revealed that there was an increase in grammar mastery among students, and average test scores changed from 71.3 in the pre-test to 83.2 in the post-test. Frame grammar within the context of real-life situations pertaining to their discipline in the vocational context increased levels of their understanding and reasoning. Initially, there were some challenges such as inconveniences emerging from lack of exposure to the PBL model and not being able to understand the videos due to limited vocabulary, but continuous reforms and assistance made it work. This research demonstrates the effectiveness of combining PBL and ESLVideo.com filling the void between language education and practice and prepares learners with the needed skills in the contemporary workforce.